Traditional Moken Ethnic Houses in the Surin Islands, Phang Nga Province, Thailand - Monsinee Attavanich; Ayako Fujieda; Chiemi Iba; Hirohide Kobayashi (My University, 2025)
Today's vernacular architecture is influenced by urban development and modernity, resulting in the originalform and accumulated knowledge gradually fading away and often being neglected. The Moken communityin the Surin Islands, Phang Nga Province, is an example of these changes. From the tsunami disaster to thefire incident, the modern influence has replaced the traditional. Even though natural materials are still used,the modern style has affected the living conditions of residents. The fire incident destroyed 60 out of 80houses, with new houses being provided. As a result, the Moken village has two forms of houses. The newlybuilt houses are constructed differently from the traditional design, changing from a nine-pillar house to afour-pillar house with cantilevered beams, designed to accommodate future expansion. However, the spacebetween the houses is narrow at only 1–1.5 meters, which limits expansion. The field survey conducted in2019 collected data on the 20 remaining houses that survived the fire to understand the type of housing thatsupports the lifestyles of Moken. Architectural characteristics, living conditions, and house modificationwere recorded to provide a database on the design of traditional houses before they disappear or arereplaced by new house styles. Such a database would also be useful for house planning in the future. Theresults of the study revealed that Moken have extensive housing knowledge. The structural systems andconstruction techniques used support house modifications. The core house with extensions supports longtermliving. There are appropriate locations for each activity taking place around the house, as well asroom for family expansion and living spaces such as bedrooms, kitchens, storage, and terrace areas. Thecore house design includes areas that support modern activities, such as shops, and shows the possiblewidth and size suitable to accommodate activities for future expansion.
Keywords: Cultural Heritage Management and Preservation